Perception of family health strategies nurses regarding the assistance to postpartum women with an indication of postpartum depression (Research, Society and Development, 2022)
Objective: To analyze the perception of nurses from Family Health Strategies regarding the assistance to puerperal women with an indication of postpartum depression, in Primary Health Care. Methodology: Exploratory study with a qualitative approach, carried out with nurses from the Family Health Team, in the Southern Triangle Region of Minas Gerais, Brazil. Data were collected from June to July 2021, using an instrument validated by judges. For data analysis, the thematic content analysis proposed by Bardin was used. Results: 31 nurses participated in the research. Signs and symptoms of Postpartum Depression perceived by the nurses of the Family Health Strategies related to the difficulty in the breastfeeding process, fears and insecurities regarding the care of the newborn were identified; and health care for puerperal women with postpartum depression, which was associated with the knowledge of professionals about postpartum depression; the nursing care provided by the nurse to the puerperal woman in this condition, the factors that facilitate and limit this care, and the importance of the multiprofessional team in the care and follow-up of the puerperal woman with indications of postpartum depression. Conclusion: It is observed that nurses feel insecure and unprepared to provide qualified assistance to postpartum women with signs of Postpartum Depression. The nurse has the role of instituting an attentive and holistic look at pregnant and postpartum women, especially for those who show a previous depression, to guarantee quality care.